Characterisation of ionic conductivity in lithium-borate glass: experimental and instructional material on impedance spectroscopy. (30th May 2023) - Benyeogor, Mbadiwe S.; Nnoli, Kosisochukwu P.; Olakanmi, Oladayo O.
This paper discusses impedance spectroscopy as a novel and effective method of characterising electrical materials and probing the dynamics of charge carriers at the interfacial layers of dielectrics. Here, an experiment is carried out to characterise the ionic conductivity (which infers resistivity) of two lithium-borate glass samples as a function of temperature, by means of impedance spectroscopy. The experiment compares or fits the impedance data to an equivalent circuit, which is a model of the underlying physical processes under investigation, and discusses the analogies between circuit elements and the processes. Analyses of the results show how the impedance of lithium-borate glass varies with temperature, between 240°C and 320°C. Moreover, this paper provides a conceptual foundation for introducing the experiment into school curricula.